The Effect of Discovery Learning Model on Students' Science Literacy - Wijaya, Agus Budi Darma; Sukroyanti, Baiq Azmi; Herayanti, Lovy (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
The purpose of this research is to determine the influence of the discovery learning model on students' science literacy. This study used a quasi-experimental research design. The population of this study consisted of all students in grade X IPA (Natural Sciences) at Senior High School 1 Sukamulia, which consisted of two classes. The sample for this study was the students of X IPA 1 as the experimental group and X IPA 2 as the control group. Based on the analysis of pretest data, the average score for the experimental group was 37.70 and the control group was 31.41. The results of the posttest showed that the average score for the experimental group was 81.90 and the control group was 76.19. The research results using the one-tailed critical t-test obtained a calculated t-value of 2.16 and a critical t-value of 1.67 at a significance level of 5%. Therefore, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. It can be concluded that there is an influence of the Discovery Learning Model on students' science literacy.